Occupational safety and health programs in the Maquiladora industry - Luis Velázquez; Nora Munguía; Javier Esquer; Andrea Zavala; Sara Ojeda; Markus Will; Bernd Delakowitz (Economic and Environmental Studies (E&ES), 2014)
Although traditionally the maquiladora industry had succeeded in strengthening the Mexican economic growth, this has been also criticized because their collateral effects not only on environment but also on working conditions of the maquiladora workers. This study has the purpose of deepening the actual understanding of the diverging occupational and safety practices undertaken in the Mexican maquiladora industry by evaluating the Safety and Health Programs in nine Maquiladoras in the cities of Mexicali, Hermosillo, and Nogales. Using the OSHA's Program Evaluation Profile (PEP) form OSHA-195, this study found evidence that the production patterns in this industry are changing toward a more sustainable system. In this context, the maintaining of safety and health programs has been important to improve working conditions on maquiladoras facilities.
Keywords: 330; Sustainable Production; occupational health; Safety and Occupational Health Programs; Maquiladoras